FAILURE ANALYSIS OF SKID PIPE LEAKS IN WALKING BEAM TYPE REHEATING FURNACE APPLICATIONS - Tripangestu, Muhamad Aldi; Zakiyuddin, Ahmad (Indonesian Journal of Engineering and Science, 2024)
This study investigates the failure of skid pipes within a walking beam reheating furnace at PT. X, Cilegon City. Visual inspection, chemical composition analysis, and corrosion rate evaluation revealed physical damages such as cracks, black and white scale deposits, bulging, and a 47% reduction in pipe thickness from the original 25 mm. The damage mechanism is initiated by high levels of Fe oxides causing corrosion with a dominant wustite (FeO) phase, and elements such as Ca, Mg, and Si contributing to scale formation. High water hardness (82.02 mg/L in pipe circulation) also supports scale formation. The LSI and RSI indices indicate highly aggressive water with high corrosiveness, causing localized overheating of the skid pipes. This increases the creep rate due to refractory damage, leading to high-temperature exposure and subsequent pipe leakage marked by bulging. Enhanced slag control within the reheating furnace, routine slag cleaning, and a review of cleaning schedules and frequencies to prevent similar failures.